Outcomes of first-generation versus second-generation drug-eluting stents in calcified coronary lesions: A meta-analysis - Rohman, Mohammad S.; Fajar, Jonny K.; Widyaningsih, Melly C.; Aziizah, Yusnia N.; Khasanah, Uswatun A.; Nendro, Farid EB.; Beting, Euphrasiane G.; Tanaem, Vini S.; Jannati, Desi; Putri, Wanda M.; Tamara, Fredo (Narra Sains Indonesia, 2025)
The choice between first-generation drug-eluting stents (DES) and second-generation DES in managing calcified coronary lesions remains a topic of debate. The aim of this study was to compare outcomes between first-generation DES and second-generation DES in patients with calcified coronary lesions. This meta-analysis study was conducted from October to November 2024. The databases used were Embase, Scopus, and PubMed. Relevant articles were collated, and data regarding outcomes in patients with calcified coronary lesions treated with first-generation and second-generation DES were included to calculate the pooled effect size. The statistical analysis was performed using the Mantel-Haenszel method. Six articles were included in the study. The results indicated that calcified coronary lesions treated with first-generation DES were associated with increased risks of all-cause mortality (Odd ratios (OR): 1.23; 95% confidence interval (95%CI): 1.05–1.45; p-Egger= 0.9346; p-Heterogeneity: 0.9720; p=0.0120), myocardial infarction (OR: 1.48; 95%CI: 1.22–1.80; p-Egger: 0.6472; p-Heterogeneity: 0.5890; p<0.0001); and target lesion revascularization (TLR) (OR: 1.47; 95%CI: 1.24–1.74; p-Egger: 0.9982; p-Heterogeneity: 0.5950; p<0.0001), in comparison with second-generation DES. In contrast, when comparing first- and second-generation DES in terms of cardiac death and major adverse cardiovascular events, a similar risk was depicted. This study compared the outcomes of first-generation and second-generation DES in the management of patients with calcified coronary lesions, which may serve as a reference for selecting DES in the patient population.